Evaluation of the Behaviours of Undergraduate Students by Using Work Sampling Method During The Time Period of a Lecture - Mücella Güner; Mehmet Küçük; Eda Acar (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2017)
Requirements of education with the globalization, rapid change in technology have effected the education institutions like other institutions. It can not be possible to think that the education system is independent of the developments and changes occurring in the other areas of the society. Education system has to train more qualitative people like using the knowledge creatively, contributing to the knowledge creation, adopting to the universal values easily because of all the developments. In this context, the focusing point is the quality and efforts to increase the quality are one of the main subject of the country agenda. To increase the quality in the system, it is important that students’ behaviours have to be evaluated and interpreted during the course then the necessary precautions have to be taken. In this research, students’ behaviours are observed and determined to increase the productivity of the course by using work sampling method which is one of the measurement technique.